A new species of the Chaleponcus dabagaensis-group from Mount Rungwe, Tanzania—support for an extended concept of the Eastern Arc Mountains (Diplopoda, Spirostreptida, Odontopygidae) - Enghoff, Henrik (Zootaxa, 2017)
Chaleponcus altirungwensis sp. nov. is described from Mount Rungwe, Tanzania. The new species belongs to the Chaleponcus dabagaensis group which is otherwise restricted to the Udzungwa Mountains and joins a growing set of taxa indicating close biogeographical connections between Mount Rungwe and the Eastern Arc Mountains in a strict sense.